Reassessing Actus Reus - Ashworth, Andrew (Victoria University of Wellington Law Review, 2023)
This article focuses on Tony Smith’s criticisms of criminal lawyers’ use of the concept of actus reus. It explores how those criticisms relate to the proliferation of types of actus reus in the last five decades, especially in connection with the spread of offences of omission.